Quantitative Determination and Validation of Metformin Hydrochloride in Pharmaceutical Using Quantitative Nuclear Magnetic Resonance Spectroscopy - H. H. Gadape; K. S. Parikh (E-Journal of Chemistry)
Rapid, specific and accurate proton nuclear magnetic resonance spectroscopy (1H NMR) method was developed to determine metformin hydrochloride antidiabetic drug in pharmaceutical tablet formulation. The method was based on quantitative NMR spectroscopy (qNMR) using maleic acid as an internal standard and deuterium oxide (D2O) as a diluent. For the quantification of the drug, the (1H NMR signals at 2.91 ppm and 6.25 ppm corresponding to the analyte proton of metformin hydrochloride and maleic acid internal reference standard (IS) respectively were used. The method was validated for the parameters of specificity and selectivity, precision and intermediate precision, linearity, range, limit of detection (LOD) and limit of quantification (LOQ), accuracy, solution stability and robustness. The linearity of the calibration curve for analyte in the desired concentration range was good (R2=0.9993). The method was accurate and precise with good recoveries. Range study was also performed up to saturation level (152.67 mg/0.60 mL) in D2O. The advantage of the method is that no reference standard of analyte drug is required for quantification. The method is nondestructive and can be applied for quantification of metformin hydrochloride in commercial formulation products.